Dynamics of user-generated content and service failure recovery: evidence from millennials - Ozuem, Wilson; Willis, Michelle; Ranfagni, Silvia; Howell, Kerry; Rovai, Serena (Emerald, 2023)
Purpose: There is considerable interest in the value of user-generated content (UGC) and its antecedents. Despite its growing importance, existing studies have largely ignored the effects of UGC on customers’ responses to recovery efforts in the fashion industry. The aim of this paper is to examine the extent to which UGC influences customers’ responses to providers’ service failure and recovery efforts, particularly how millennials’ interactions impact recovery efforts.